Helper Syndrome and Pathological Altruism in nurses – a study in times of the COVID-19 pandemic - Maringgele, Victoria E.; Scherr, Martin; Aichhorn, Wolfgang; Kaiser, Andreas K. (Frontiers in Psychology, 2023)
Background Pathological Altruism and the concept of Helper Syndrome are comparable. We focused on Schmidbauer’s description because it provides a comprehensive and testable definition. Nevertheless, this concept of Helper Syndrome has not yet been empirically investigated in a sample of helping professionals. Aim To investigate whether nurses working with covid-19 patients are more likely to have Helper Syndrome compared with individuals from non-helper professions. Methods The online survey took place between April 2021 and February 2022, in urban and rural regions of Salzburg, during the time of the COVID-19 pandemic. Nurses (n = 447) and controls (n = 295) were compared regarding Helper Syndrome characteristics. To measure characteristics of Helper Syndrome the following questionnaires were used: WHO-Five (WHO-5), selected scales of the Personality, Style and Disorder Inventory (PSSI) and the Freiburg Personality Inventory-Revised (FPI-R), the Alcohol Use Disorders Identification Test (AUDIT). Insecure gender identity and self-assessment of having a Helper Syndrome was measured by a Likert scale. Results In both groups, Helper Syndrome was detected (nurses 29.5%, controls 30.5%). Participants with Helper Syndrome showed significant differences in personality styles and traits, namely significantly higher scores for Foreboding-Schizotypical Personality Style, Spontaneous-Borderline Personality Style, Amiable-Histrionic Personality Style, Ambitious-Narcissistic Personality Style, Loyal-Dependent Personality Style, Helpful-Selfless Personality Style, Carefully-Obsessive Personality Style, Optimistic-Rhapsodic Personality Style, Social Orientation, Strain, Emotionality and lower well-being. The only difference between nurses and controls was that nurses were significantly less open aggressive. Conclusion For the first time, we were able to demonstrate Schmidbauer’s concept of Helper Syndrome. According to our data, we found a subgroup of individuals similar to Schmidbauer’s description of Helper Syndrome, but this sample was independent of helping or non-helping profession. These individuals seem to be at higher risk for psychiatric disorders.